Population Structure, Antimicrobial Resistance, and Virulence-Associated Genes in Campylobacter jejuni Isolated From Three Ecological Niches: Gastroenteritis Patients, Broilers, and Wild Birds - Iglesias-Torrens, Yaidelys; Miró, Elisenda; Guirado, Pedro; Llovet, Teresa; Muñoz, Carmen; Cerdà-Cuéllar, Marta; Madrid, Cristina; Balsalobre, Carlos; Navarro, Ferran (Frontiers in Microbiology, 2018)
Campylobacter jejuni is the causal agent of the food-borne infection with the highest incidence in Europe. Both poultry and wild birds are a major reservoir. To gain insight into the population structure, virulence potential and antimicrobial resistance (AMR), a collection of 150 isolates from three different ecological niches (broilers, wild birds and human patients) was studied. Despite the high genetic diversity found, the population structure defined two distinct clusters, one formed mostly by broiler and human isolates and another one by most wild bird isolates. The ST-21complex exhibits highest prevalence (in humans and broilers), followed by ST-1275complex (only in wild birds). The ST-48, -45 and -354 complexes were found in all three niches, but represent only 22 out of 150 studied strains. A higher occurrence of AMR and multidrug resistance was detected among broiler and human isolates. Moreover, significant differences were found in the distribution of certain putative virulence genes. Remarkably, many wild bird strains were negative for either cdtA, cdtB or cdtC from the canonical strain 81-176, whereas all broiler and human strains were positive. These data suggest that the different variants of the cdt genes might be relevant for the efficient colonization of certain hosts by C. jejuni. Our study contribute to the understanding of the role of the diverse Campylobacter reservoirs in the transmission of campylobacteriosis to humans.